APLIKASI 3D ARTERIAL SPIN LABELING SEQUENCE PADA PEMERIKSAAN BRAIN MRI - Nova Setiyanto, Ary; Nur Mayani, Anita (JRI (Jurnal Radiografer Indonesia), 2020)
Background: MRI (Magnetic Resonance Imaging) is a noninvasive diagnostic examination that utilizes high magnetic field strength in producing an image. Non-contrast Brain MRI Examination in Radiology Installation of Adi Husada Undaan Wetan Hospital Surabaya using a sequence of Ax DWI b1000 routines, Ax T2 Flair FS, Ax T2 Propeller, Ax T1 FSE, MRA TOF, Ax T2 * GRE. Clinical suspect CVA infarct, Brain MRI examination in Radiology Installation of Adi Husada Hospital Undaan Wetan Surabaya added 3D ASL sequences without using gadolinium contrast media. Methods: This type of research is qualitative research with a case study approach. Data was taken from January to February 2019. The object of the study was MRI Brain examination in CVA infract cases at Radiology Installation at Adi Husada Undaan Wetan Hospital, Surabaya. The research subjects are 2 radiographers and 1 radiologist. Results: Based on the results of visual analysis with interview methods with radiologists, the image results on Ax DWI b1000, Ax T2 Flair FS and Ax T2 Propeller appear hyperintense images which indicate the presence of pathology in the restricted area. The addition of the 3D ASL sequence is used to determine CBF (cerebral blood flow). Conclusions : The application of the 3D ASL sequence to the clinical suspect CVA infarct with the right method can greatly assist the radiologist to diagnose patient abnormalities.